2021
DOI: 10.1097/psy.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Biofeedback Intervention on Heart Rate Variability in Individuals With Panic Disorder: A Randomized Controlled Trial

Abstract: ObjectiveSome individuals with panic disorder (PD) display reduced heart rate variability (HRV), which may result in an increased risk of cardiovascular mortality. Heart rate variability–biofeedback (HRV-BF) training has been shown to improve the modulation of the autonomic activity. Therefore, this randomized controlled trial was conducted to investigate the effect of a 4-week HRV-BF intervention in individuals with PD. HRV-BF training improved the modulation of the autonomic activity. Therefore, with this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Mediational and temporal analyses from prior panic and anxiety trials with CART support this notion in that the correction of sustained hypocapnia by therapeutically increasing P co 2 levels mediated improvements in panic symptoms, symptom appraisal, and perceived control (75,98,99). Trainings such as heart rate variability biofeedback have not demonstrated mediational evidence for heart rate variability and P co 2 (100) or do not assess P co 2 (101) despite proposing hyperventilation-reducing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mediational and temporal analyses from prior panic and anxiety trials with CART support this notion in that the correction of sustained hypocapnia by therapeutically increasing P co 2 levels mediated improvements in panic symptoms, symptom appraisal, and perceived control (75,98,99). Trainings such as heart rate variability biofeedback have not demonstrated mediational evidence for heart rate variability and P co 2 (100) or do not assess P co 2 (101) despite proposing hyperventilation-reducing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this finding aligns with previous studies reporting an increase in SDNN after HRV-BF intervention in other disorders (e.g., Refs. (20,54)). In a secondary analysis of this HRV-BF intervention, we analyzed within-session HRV changes and observed that participants learned to increase their HRV (48).…”
Section: Discussionmentioning
confidence: 99%
“…Studies were published between 1984 and 2022 (Figure 3). Regarding site location, eight (50%) studies were conducted in the United States [53][54][55][56][57][58][59][60], three (19%) in England [61][62][63], and one (6%) in each of The Netherlands [64], Italy [65], Belgium [66], Germany [67], and Japan [68]. Table 3 presents details on the publication year, geographic location, study design, study population (clinical diagnosis, number of patients, sex, and age), breathwork technique (style and methods), and breathwork protocol (duration of sessions, frequency, treatment period, and follow-up).…”
Section: Publication Analysismentioning
confidence: 99%